2003
DOI: 10.1074/jbc.m202347200
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial and Nuclear Localization of Topoisomerase II in the Flagellate Bodo saltans (Kinetoplastida), a Species with Non-catenated Kinetoplast DNA

Abstract: We have studied topoisomerase II (topo II) in the cells of Bodo saltans, a free-living bodonid (Kinetoplastida). Phylogenetic analysis based on the sequence of the entire topo II gene, which is a single-copy gene, confirmed that B. saltans is a predecessor of parasitic trypanosomatids. Antibodies generated against either an overexpressed unique C-terminal region of topo II or a synthetic oligopeptide derived from the same region did not cross-react with cell lysates of related trypanosomatids, while they recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…So far, only a few individual enzymes have been described and characterized in B. saltans (Brown et al. ; Gažiová and Lukeš ; Jackson et al. ; Lawrie ), and the RNA editing machinery performing insertions and/or deletions of uridines is apparently present in its mitochondrion (Blom et al.…”
Section: Genomic Sequences Used In the Analysismentioning
confidence: 99%
“…So far, only a few individual enzymes have been described and characterized in B. saltans (Brown et al. ; Gažiová and Lukeš ; Jackson et al. ; Lawrie ), and the RNA editing machinery performing insertions and/or deletions of uridines is apparently present in its mitochondrion (Blom et al.…”
Section: Genomic Sequences Used In the Analysismentioning
confidence: 99%
“…By contrast, the antiserum raised against the recombinant T. cruzi located topoII in the nucleus of T. cruzi and C. fasciculata (Fragoso et al , 1998). In Leishmania donovanni and Bodo saltans , polyclonal antibodies raised against their respective topoII enzymes, labeled both the kinetoplast and the nucleus, suggesting that the same enzyme is present in both compartments (Das et al , 2001; Gaziová & Lukes, 2003). We have also shown that DNA gyrase inhibitors cause dramatic changes in the kDNA network, suggesting that topoisomerase II is important for maintaining the kDNA structure (Cavalcanti et al , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Topoisomerase activity has been observed in a number of kinetoplastida, including Trypanosoma cruzi (Douc‐Rasy et al , 1986), Leishmania donovani (Chakraborty and Majumder, 1987) and Crithidia fasciculata (Melendy & Ray, 1989). Furthermore, TOP2 genes have been characterized for Trypanosoma brucei (Strauss & Wang, 1990), T. cruzi (Fragoso & Goldenberg, 1992), C. fasciculata (Pasion et al , 1992), L. donovani (Das et al , 2001), L. infantum (Hanke et al , 2003) and Bodo saltans (Gaziová & Lukes, 2003).…”
Section: Discussionmentioning
confidence: 99%